EFFECT OF DEXAMETHASONE VERSUS PLACEBO FOR IMPROVED RECOVERY IN PATIENTS UNDERGOING ANAESTHETIC INTERVENTIONS FOR GENERAL SURGICAL PROCEDURES - Malik, Sara Haider; Begum, Nighat; Ashfaq, Allah Ditta; Saleem, Huma; Shah, Muhammad Tariq; Hanif, Muhammad; Abbasi, Tariq (Journal of Ayub Medical College Abbottabad, 2019)
Background: Endotracheal intubation is one of the basic prerequisites of general anaesthesia. Recovery of patients is delayed due to the development of post-operative nausea, vomiting, sore throat and shivering. This study was conducted to determine role of dexamethasone for improved recovery of patients. Methods: This randomized controlled trial was performed in the Department of Anaesthesia, Ayub Teaching Hospital, Abbottabad from June to November 2018. One hundred and twenty-two consenting patients of both genders, aged between 18-60 years, American Society of Anaesthesiologists (ASA) I and II, scheduled for general surgeries of 60-180 minutes duration under general anaesthesia were included. Patients with long duration surgeries, anticipated difficult airways, nasogastric tube in situ, upper respiratory tract infections, on steroid therapy and critically ill and emergency surgeries were excluded. They were randomly allocated into two groups by lottery method as dexamethasone (group A, n=61) or Placebo (group B, n=61). Post-operative nausea, vomiting, sore throat was observed at 2, 12 and 24 hours, shivering was observed at 2 hours only and patient satisfaction at 24 hours post-operatively. Results: Group A patients had statistically proven better outcomes at 2, 12 and 24 hours for post-operative sore throat, nausea and vomiting, shivering was controlled in 24.5% p-value (0.006). Patient satisfaction was found in 83.6% of group A patients. Conclusion: Thus, dexamethasone is effective drug for prevention of postoperative nausea, vomiting, sore throat and shivering in general surgical procedures thus improving patient satisfaction and their early discharge. Keywords: Dexamethasone; sore throat; nausea; vomiting; shivering; patient satisfaction